2015
DOI: 10.1111/aos.12740
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal blood pressure in primary open‐angle glaucoma

Abstract: ABSTRACT.Purpose: To evaluate the nocturnal blood pressure (BP) dipping-pattern in patients with manifest primary open-angle glaucoma (POAG) and to find possible associations with the severity of visual field damage. Methods: A number of 314 patients suffering from POAG were consecutively enrolled in this cross-sectional hospital-based study. Each patient had diurnal intraocular pressure (IOP) measurements, 24-hr BP monitoring and computerized perimetry with the Humphrey 30-2 SITA Standard program. Inclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
1
12
0
3
Order By: Relevance
“…DOPP is especially useful for displaying the lowest OPP values and is regarded as an independent risk factor for OAG. A recent study suggested that nocturnal BP could be a modifiable risk factor for glaucoma severity and progression [ 63 ]. Nocturnal hypotension is caused primarily by sleep, presumably owing to sympathetic withdrawal.…”
Section: Poag and Hypotensionmentioning
confidence: 99%
“…DOPP is especially useful for displaying the lowest OPP values and is regarded as an independent risk factor for OAG. A recent study suggested that nocturnal BP could be a modifiable risk factor for glaucoma severity and progression [ 63 ]. Nocturnal hypotension is caused primarily by sleep, presumably owing to sympathetic withdrawal.…”
Section: Poag and Hypotensionmentioning
confidence: 99%
“…In contrast, more recent reports, as Maracaibo Aging Study, suggest that it is not the physiological nocturnal hypotension that triggers optic nerve damage, but rather the non-physiological overdipping pattern of more than 20% [14]. Similar findings were presented by Pillunat et al [23], who suggested that normotensive (but not hypertensive) patients with an over-dipping pattern of ABP have an increased risk of glaucoma progression.…”
Section: Low Blood Pressure and Glaucomamentioning
confidence: 57%
“…DOPP is particularly useful in displaying the lowest OPP values and is seen as a free risk factor for OAGs. A continuous report suggests that evening BP could be a modifiable risk factor for the truth and growth of glaucoma [9].…”
Section: Discussionmentioning
confidence: 99%